Boundaries adrift: entitlements and delimitation in shifting seas - Jain, VR (2022)
Sea-level rise threatens to undermine the legal order of the oceans. By causing a retreat in the shoreline, it can submerge critical basepoints and alter the status of features from which entitlement limits and delimited boundaries are measured. This issue has received significant academic attention, yet much of it is dedicated to the study of adaptation. The consensus is that the existing legal framework will have to be replaced by one that provides for stable baselines and limits. This thesis does not deny the need for adaptation. However, it argues for an enhanced focus on resilience. Recognizing that new rules to address sea-level rise will require significant time to be adopted, the thesis explores what coastal states can do, under existing law, to stabilize their maritime claims. Examining the United Nations Convention on the Law of the Sea, the thesis unearths significant resilience within its provisions. It argues that the ambulation of the normal baseline under Article 5 is not automatic but is controlled by the coastal state through the revision of charts. It demonstrates how vertical datum calculations could be used to tether the movements of the charted baseline. It offers a doctrinal justification for the construction of straight baselines on coasts impacted by sea-level rise under Article 7(2). It uncovers the legal basis for the use of coastal fortification measures to stabilize the baseline within Article 11. It justifies why continental shelf limits are resilient to the effects of sea-level rise, determining that there are two routes to their permanence under Article 76(8) and Article 76(9). Finally, it reveals that the opposability of delimited boundaries cannot be successfully challenged in the context of sea-level rise due to their status as executed treaty provisions. The doctrinal limits to which the Convention’s provisions may be applied are also studied. The thesis identifies each measure as one with promising yet finite utility. It concludes by outlining a plan of action that coastal states may follow to enhance the resilience of their maritime claims, based on the preceding legal analysis.